200k views
0 votes
Find the value of x when 6 - 3x = 5x - 10x + 6.
The value of x is ?

2 Answers

2 votes

Explanation:

6-6 = 5x - 10x +3x

0= - 2x

Divide both sides by -2

X = 0/-2x

I think that is the answer

User Eddinho
by
6.1k points
4 votes

6 - 3x = 5x - 10x + 6

combine like terms

6 - 3x = -5x + 6

subtract 6 from both sides

-3x = -5x

x = 0

User Paul Sandoz
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.